The adult ADHD assessment quality assurance standard - Adamou, Marios; Arif, Muhammad; Asherson, Philip; Cubbin, Sally; Leaver, Laurence; Sedgwick-Müller, Jane; Müller-Sedgwick, Ulrich; van Rensburg, Kobus; Kustow, James (Frontiers in Psychiatry, 2024)
Background: Attention Deficit Hyperactivity Disorder (ADHD) frequently persists into adulthood. There are practice guidelines that outline the requirements for the assessment and treatment of adults. Nevertheless, guidelines specifying what constitutes a good quality diagnostic assessment and report and the competencies required to be a specialist assessor are lacking. This can lead to variation in the quality and reliability of adult ADHD assessments. Poor quality assessments may not be accepted as valid indicators of the presence of ADHD by other clinicians or services, resulting in wasteful re-assessments and delays in providing treatment. To address this issue the UK Adult ADHD Network (UKAAN) proposes a quality framework for adult ADHD assessments -the Adult ADHD Assessment Quality Assurance Standard (AQAS).The co-authors agreed on five questions or themes that then guided the development of a set of consensus statements. An initial draft was reviewed and amended in an iterative process to reach a final consensus.What constitutes a high-quality diagnostic assessment and report was agreed by consensus of the co-authors. The resulting guideline emphasises the need to evaluate impairment, describes core competencies required by the assessor and highlights the importance of linking the diagnosis to an appropriate post-diagnostic discussion. Assessments should be completed in the context of a full psychiatric and neurodevelopmental review, and need good interview skills, using a semi-structured interview with open questioning and probing to elicit real life examples of symptoms and impairments. It is recommended that 2 hours or more is required for an adequate assessment including both the diagnostic assessment and initial post-assessment discussions.The AQAS has been developed as a practical resource to support reliable and valid diagnostic assessments of adult ADHD. It is intended to complement formal training. A secondary objective is to empower patients by providing them with evidence-based information on what to expect from an assessment and assessment report.